Pengaruh Profitabilitas, Leverage, Kepemilikan Institusional Dan Struktur Aset Terhadap Harga Saham - Fanisa Maharani Bay; Agus Endro Suwarno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze the effect of profitability, leverage, institutional ownership, and asset structure on stock prices in manufacturing companies for the period 2020-2022. The population in this study used manufacturing companies listed on the Indonesia Stock Exchange (IDX). A total of 228 samples were collected using purposive sampling method. The data analysis method in this study is multiple linear regression. The results showed that profitability has a significant impact on stock prices, as indicated by a sig value of 0.000 <0.05. Leverage has no significant effect on stock prices, as indicated by a sig value of 0.846> 0.05. Institutional ownership has a significant effect on stock price, as indicated by a sig value of 0.038 < 0.05. Asset structure has no significant effect on stock price, as indicated by a sig value of 0.200 > 0.05.